The human condition - Arendt, Hannah (The University of Chicago Press, 1958)
This book is extraordinarily accessible and thought-provoking for undergraduate students. I have used it in my course on twentieth-century women philosophers. Arendt, without citing Husserl or Heidegger, enacts what I would call a phenomenology of action. That is, she examines the experience of the vita activa (or life of action) by describing it on its own terms. For Arendt, Marx and Smith were wrong to say that human life is fundamentally about labor or about skilled work. Human life is not mostly for or about the consumption of commodities and entrenching one's family ties. Rather, human life is about establishing a public, political realm that emulates (but does not simply attempt to reproduce) the Greek polis. Humanity is about opening up a space for meaning and for evanescent but important co-creation of what counts as a good life. For Arendt, action is fragile, frail, unpredictable, and irreversible. Action appreciates the differences between humans within the outlines of a nation, for example, and action does not simply attempt to compel others to yield to a single, sovereign will. Action calls those who participate in true politics to realize the sense of 'e pluribus unum' and to make sure that the plurality or 'pluribus' is not simply a fading memory in the face of the One.